Transcriptome analysis reveals key drought-stress-responsive genes in soybean - Li, Mingqian; Li, Hainan; Sun, Anni; Wang, Liwei; Ren, Chuanyou; Liu, Jiang; Gao, Xining (Frontiers in Genetics, 2022)
Drought is the most common environmental stress and has had dramatic impacts on soybean (Glycine max L.) growth and yield worldwide. Therefore, to investigate the response mechanism underlying soybean resistance to drought stress, the drought-sensitive cultivar “Liaodou 15” was exposed to 7 (mild drought stress, LD), 17 (moderate drought stress, MD) and 27 (severe drought stress, SD) days of drought stress at the flowering stage followed by rehydration until harvest. A total of 2214, 3684 and 2985 differentially expressed genes (DEGs) in LD/CK1, MD/CK2, and SD/CK3, respectively, were identified by RNA-seq. Weighted gene co-expression network analysis (WGCNA) revealed the drought-response TFs such as WRKY (Glyma.15G021900, Glyma.15G006800), MYB (Glyma.15G190100, Glyma.15G237900), and bZIP (Glyma.15G114800), which may be regulated soybean drought resistance. Second, Glyma.08G176300 (NCED1), Glyma.03G222600 (SDR), Glyma.02G048400 (F3H), Glyma.14G221200 (CAD), Glyma.14G205200 (C4H), Glyma.19G105100 (CHS), Glyma.07G266200 (VTC) and Glyma.15G251500 (GST), which are involved in ABA and flavonoid biosynthesis and ascorbic acid and glutathione metabolism, were identified, suggesting that these metabolic pathways play key roles in the soybean response to drought. Finally, the soybean yield after rehydration was reduced by 50% under severe drought stress. Collectively, our study deepens the understanding of soybean drought resistance mechanisms and provides a theoretical basis for the soybean drought resistance molecular breeding and effectively adjusts water-saving irrigation for soybean under field production.